The Role of Schools in Building a Literacy Culture through Support for Reading Motivation and Interest - Sujarwoko, Sujarwoko; Rahmayantis, Marista Dwi; Suhartono, Suhartono; Khoiriyah, Khoiriyah; Azizah, Sherly Nur; Ilma, Alfika Fatkhiyatul (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
Literacy culture is not only demonstrated through reading activities at school or in certain formal programs but also through reading habits within families and communities, which occur naturally without being perceived as school assignments. Therefore, schools need to provide support for students’ motivation and interest in reading so that literacy culture can develop sustainably. This study aims to examine: (1) access to information resources, (2) reading habits, (3) the quality of reading materials, and (4) students’ motivation and interest in reading. The research design employed a descriptive approach by combining quantitative data from questionnaires with narrative analysis. The subjects of this study were 239 students of MTs Miftahul Huda, Jambu Village, Plemahan District, Kediri Regency, selected through a total sampling technique. The research instrument was a questionnaire distributed via Google Form, while data analysis was carried out through reduction, data presentation, and conclusion drawing. The findings indicate that access to information resources is relatively adequate in terms of libraries and reading materials, although digital literacy still needs strengthening. Reading habits are categorized as moderately active to active, the quality of reading materials is rated as good, and students’ motivation and interest in reading are considered high. This study concludes that strengthening digital literacy, providing contextual reading materials, and implementing collective appreciation strategies are necessary to develop a more balanced and sustainable literacy culture.